'Echoes from the Field' Study Outcome and Discussion: Reflections on Software Systems Engineering Practice. Issue 1 (13th September 2016) - AlQaisi, Raid; Gray, Edwin; Moffat, David; Wang, Bo
Abstract: To date, despite that various software development approaches have evolved and demonstrated success, many software development projects still fail. This paper argues that the reason for such failure is the result of not addressing the human‐side of the Software Systems Engineering (SWSE) adequately. Humans are relatively unpredictable components in the larger system of the sociotechnical environment, therefore requires adequate consideration. The study investigated the experience and perception of software engineers for the contemporary practice of SWSE. A suite of multidisciplinary theories was consulted and adapted to broaden the understanding of the role human‐element plays in SWSE, such as the Knowledge Creation Theory (KCT), Toyota Production System (TPS) known as "Lean" and Emotional Intelligence (EI). An overall conclusion is that SWSE is a human‐centric activity, and its success is heavily reliant on the human‐element and its related social dynamics. The findings can help viewing SWSE from a different prospective that could help improving the practice.